2014
DOI: 10.3389/fimmu.2014.00238
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells: Neglected Regulators of the Immune Response to Staphylococcus aureus

Abstract: Plasmacytoid dendritic cells (pDC) are a rare subset of leukocytes equipped with Fcγ and Fcε receptors, which exert contrary effects on sensing of microbial nucleic acids by endosomal Toll-like receptors. In this article, we explain how pDC contribute to the immune response to Staphylococcus aureus. Under normal circumstances the pDC participates in the memory response to the pathogen: pDC activation is initiated by uptake of staphylococcal immune complexes with IgG or IgE. However, protein A-expressing S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 140 publications
4
12
0
Order By: Relevance
“…2 C). This result is consistent with previous reports that showed a marked capacity for macrophages to produce IFN-β in response to S. aureus bacterial infection, whereas IFN-α is generally secreted by plasmacytoid dendritic cells after bacterial infection 5 , 54 .
Figure 2 Purified S. aureus MVs induce significant IFN-β mRNA expression in cultured murine macrophages.
…”
Section: Resultssupporting
confidence: 93%
“…2 C). This result is consistent with previous reports that showed a marked capacity for macrophages to produce IFN-β in response to S. aureus bacterial infection, whereas IFN-α is generally secreted by plasmacytoid dendritic cells after bacterial infection 5 , 54 .
Figure 2 Purified S. aureus MVs induce significant IFN-β mRNA expression in cultured murine macrophages.
…”
Section: Resultssupporting
confidence: 93%
“…2C). This result is consistent with previous reports that showed a marked capacity for macrophages to produce IFN-β in response to S. aureus bacterial infection, whereas IFN-is generally secreted by plasmacytoid dendritic cells after bacterial infection 5,53 .…”
Section: Introductionsupporting
confidence: 93%
“…Although pDCs phagocytose particulate Ag more efficiently than soluble Ag, pDCs were still inferior to cDCs in phagocytosing particulate Ag, including apoptotic and necrotic cells . However, pDCs can uptake bacteria by Ag‐specific IgG and IgE via FcγRIIa and FcεRI, and modulate memory responses . In this study, as shown in Supplementary figure 2b, we demonstrate that pDCs are inferior to mDCs in capturing soluble Ags in BALB/c mice, which is in agreement with previous reports.…”
Section: Discussionsupporting
confidence: 92%